Islamic Wasatiyyah Teaching in Indonesian Education: An Analysis of the Tasawuf Approach - Gani, A. (Opción, 2019)
The objective of this qualitative study is to focus on the role played by the Wasatiyyah concept in Indonesian Education via the exploratory content analysis method. For this purpose, the study analyzed the Tasawuf approach, the Islamic mysticism. As a result the educational institutions included such principles like good (khayr) and bad (fasad) or just and moderation as part of the Indonesian curricula. In conclusion, it can be concluded that the Wasatiyyah concept applied in the Indonesian education is in tandem with the Tasawuf approach considered as the main element of Islamic epistemology.